Evaluation of Resins for Stereolithographic 3D-Printed Surgical Guides: The Response of L929 Cells and Human Gingival Fibroblasts. (22nd October 2017) - Kurzmann, Christoph; Janjić, Klara; Shokoohi-Tabrizi, Hassan; Edelmayer, Michael; Pensch, Manuela; Moritz, Andreas; Agis, Hermann
Abstract : Additive manufacturing is becoming increasingly important in dentistry for the production of surgical guides. The development of cost-effective desktop stereolithography (SLA) printing systems and the corresponding resins makes this novel technique accessible to dental offices and dental laboratories. The aim of the study was to reveal the response of soft tissue cells to Clear and Dental SG resins used in desktop SLA printing systems at different stages of processing. Cell activity of L929 cells and gingival fibroblasts (GF) in response to the materials was examined in indirect and direct monolayer culture models and a direct spheroid culture model based on MTT, resazurin-based toxicity assays, and live-dead staining. Overall we found that the impact of Clear and Dental SG resins on L929 and GF depends on the processing stage of the materials. Liquid Clear resin induced a stronger reduction of cell activity compared to Dental SG resin. Printing and postcuring reduced the impact on cell activity and viability. As in-house 3D printing for surgical guides is getting integrated in the digital workflow, our data suggest that careful adherence to processing guidelines—especially postcuring—is of clinical relevance.